Respuesta :
Answer:
Inverse of given function = log(x)/log(3)
Step-by-step explanation:
How to find the inverse of any function?
- In the complete function, replace y with "x" and x with "y"
- Then, solve the obtained equation from step 2 for y
- And, then the value obtained for "y" is the inverse required i.e. = f^{-1}(x)
Now, we solve the problem:
Given :- y = 3^x
replacing the value of "y" with "x", we get,
x = 3^y
to solve for "y" we should take the "logarithm" for both sides
log (x) = y log(3)
or y = log(x)/log(3)
or f^(-1) (x) = log(x)/log(3)